Cross Test of ICT-TB and Genexpert Examination in Suspected Cases of M. tuberculosis Infection at Bima Regency Regional Hospital - Wiadnya, Ida Bagus Rai; Sani, Syahrul; Srigede, Lalu (Poltekkes Kemenkes Mataram, 2025)
GeneXpert is able to detect specimens that are positive for M. tuberculosis in a shorter time and with high sensitivity and specificity. ICT-TB is used to detect the presence of antibodies produced by M. tuberculosis infection in the body. This response requires time to form. However, actually ICT-TB is an easier method compared to Genexpert. So this research was carried out to compare the results of the two methods. Research Objective: To determine the results of cross-testing of ICT-TB and Genexpert examinations on cases of suspected M. tubeculosis infection at the Bima Regency Hospital. Research Method: This is an analytical observational study with a cross-sectional design. The samples used in this research were 52 samples and the data were analyzed descriptively. Research Results: The distribution of suspected tuberculosis based on gender is 54% male and 46% female. Based on age group, Toddlers 13.5%, Children 11.5%, Teenagers 9.6%, Adults 44.2% and Elderly 21.2%. ICT-TB examination results are negative. Examination with Genexpert on the same patient was negative. Conclusion: From the results of research using ICT-TB and GeneXpert in patients with suspected M. tuberculosis infection, negative results were obtained.